Analisis Serangan Keamanan Informasi Pribadi Pada Media Sosial Facebook Menggunakan Metode National Institute of Justice (NIJ) - Khairani Rahmatul Ummah; Dahliyusmanto Dahliyusmanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Social media is very important in everyday life. However, when used, a lot of personal data and information is shared. This risks being vulnerable to personal data leaks. Facebook is one of the social media that often experiences user data leaks. There are many ways to steal Facebook user data, one of which is by using Phishing techniques. Phishing means tricking a user into entering a username, password, or other personal data on a modified site. This research was conducted regarding Phishing attacks. The method used is the National Institute of Justice (NIJ). The stages flow starts from the preparation stage, the collection stage, the examination stage, the analysis stage, and the reporting stage. The Wireshark application was used to search for evidence, and the Hashcalc application was used to acquire the obtained evidence. Keywords: Facebook, phishing, cybercrime, Wireshark.